Trapping of small organisms moving randomly : principles and applications to pest monitoring and management /: principles and applications to pest monitoring and management. ([2015]) - Miller, James R; Adams, Christopher G; Weston, Paul A (Paul Adam); Schenker, Jeffrey H
No abstract available